Tumors and tumor-like lesion of the oral cavity: A study of 100 cases at tertiary care hospital - Shaikh Parvin Abdul Rauf; Bharat R Sonwane (Tropical Journal of Pathology and Microbiology, 2020)
Introduction: Oral cancer is a major health problem in some parts of the world especially developing countries. Oral cancer is the sixth most common cancer in the world whereas in India it is the most prevalent cancer. In India increase in incidence is seen in states like Uttar Pradesh, Madhya Pradesh, Gujarat, Bihar, and Maharashtra.Material & Methods: A total of 100 cases have been studied over a period of two years & two months. The surgical pathology specimens received for histopathological diagnosis were examined microscopically, and the diagnosis was confirmed.Results: Amongst 100 cases studied, 72 (72%) cases were malignant, 12(12%) were benign, 12 (12%) were tumor-like lesions and 4 (4%) cases were premalignant conditions. The youngest patient was 4 years of age and the oldest of 84 years. The male: female ratio was2.3:1. Tobacco chewing was the commonest habit observed in patients with a malignant tumor. Buccal mucosa was the commonest site of tumors and tumor-like lesions.Conclusions: It is the need of the hour to create awareness among people about the early approach to hospital, maintenance of oral hygiene by cultivating good oral habits, and periodic oral check-ups.